Enhancing Educational Leadership Through School-Based Management: A Strategic Approach - Simatupang, Umy Nadrah; Arneti, Reni; Esisuarni, Esisuarni; Nellitawati, Nellitawati; Yahya, Yahya (Postgraduate School, Universitas Negeri Padang, 2024)
The implementation of SBM aims to empower educational institutions to manage independently, increase cooperation with related parties, and increase school accountability and transparency. This study explores the impact of SBM implementation on educational practice through a strategic leadership approach. Using library research methods, this research analyzes the contribution of SBM in improving the effectiveness of school management, focusing on the key role of school principals in leading initiatives and managing resources optimally. The research results show that effective leadership from the school principal plays a central role in the successful implementation of SBM, through active involvement in achieving the set goals and building commitment with relevant stakeholders.